Midterm outcomes of venovenous extracorporeal membrane oxygenation as a bridge to lung transplantation: Comparison with nonbridged recipients. Issue 4 (20th January 2022) - Sef, Davorin; Verzelloni Sef, Alessandra; Trkulja, Vladimir; Raj, Binu; Lees, Nicholas J.; Walker, Christopher; Mitchell, Jerry; Petrou, Mario; De Robertis, Fabio; Stock, Ulrich; McGovern, Ian
Abstract: Objectives: Venovenous extracorporeal membrane oxygenation (VV‐ECMO) is increasingly being used in acutely deteriorating patients with end‐stage lung disease as a bridge to transplantation (BTT). It can allow critically ill recipients to remain eligible for lung transplants (LTx) while reducing pretransplant deconditioning. We analyzed early‐ and midterm postoperative outcomes of patients on VV‐ECMO as a BTT and the impact of preoperative VV‐ECMO on posttransplant survival outcomes. Methods: All consecutive LTx performed at our institution between January 2012 and December 2018 were analyzed. After matching, BTT patients were compared with nonbridged LTx recipients. Results: Out of 297 transplanted patients, 21 (7.1%) were placed on VV‐ECMO as a BTT. After matching, we observed similar 30‐day mortality between BTT and non‐BTT patients (4.6% vs. 6.6%, p = .083) despite a higher incidence of early postoperative complications (need for ECMO, delayed chest closure, and acute kidney injury). Furthermore, preoperative VV‐ECMO did not appear associated with 30‐day or 1‐year mortality in both frequentist and Bayesian analysis (odds ratio [OR]: 0.35, 95% confidence interval: 0.03–3.49, p = .369; OR: 0.27, 95% credible interval: 0.01–3.82, p = 84.7%, respectively). In sensitivity analysis, both subgroups were similar in respect to 30‐day (7.8% vs. 6.5%, p = .048) and 1‐year mortality (12.5% vs. 18%, p = .154). Conclusions: Patients with acute refractory respiratory failure while waiting for LTx represent a high‐risk cohort of patients. VV‐ECMO as a BTT is a reasonable strategy in adult patients with acceptable operative mortality and 1‐year survival comparable to non‐BTT patients.